(untitled) - Wolf, Ken (New York, 1994)
PERSONALITIES AND PROBLEMS is intended as a brief and inexpensive supplementary text for the first half of the World civilizations course. This text is a collection of original essays profiling men and women who have had a significant impact on their own society and the world at large. The "personalities" range from Hammurabi to Chi Minh. Rather than being mere biographical sketches, the essays take a truly cross-cultural, interdisciplinary approach: each chapter discusses the lives of two historical figures (near contemporaries) whose careers illustrate different solutions to a common problem or issues. This comparative approach will find favor among World civilization professors who typically prefer to teach the course in this manner but who are restricted to using the available main texts which discuss different nations individually, in a piecemeal and unrelated fashion. This book, unlike other texts, ties the material together for students in a lively and accessible way. Beginning of the chapter questions help students identify the key problems or issues.
Keywords: Biography,Civilization; History